A nasalização variável de vogais na fala manauara - Martins, Joyce Camila (2018)
The nasalization of Vowels in Brasilian Portuguese is a linguistic phenomenon which understanding has fomented productive scientific discussion focusing on it’s performance and analysis. The scientific literature is unanimous in the occurrence of two nasal processes in a vocalic context: the contrastive nasality and allomorphic vowel nasality. The focus of this research is the allomorphic vowel nasality and it has multiple technical nomenclature, which is named as “variable nasalization” in this study. This research is about the description of phonetic processes, phonological and extrassist applicable in order to check the occurrence of variable nasalization in the Manauara speech, a place which presents several linguistic influences, but exhibits geographical isolation in relation to the most important commercial areas and cultural in Brazil. In order to achieve this goal, it is used the theoretical assumptions of Autosegmental Phonology, bringing into account, therefore, the nasal features apart of the sound segment; to the same purpose, searching for the assumptions theoretical-methodological of Variationist Sociolinguistics, the methodology that leads data collect and analysis of extrassist aspects. This research is divided into four sections: in the first one, a theoretical overview about the variable nasalization through different aspects of phonetic and phonological studies were developed; the second one presents the speech community, which is the base of this study; the third section is about methodological assumptions, applying Labov’s Variationist Sociolinguistic to the linguistic phenomenon, which is the subject of this research; the last one, finally presents the analysis of collected sound material. Through this material, it was noticed that variable nasalization is a phenomenon presenting in Manauara speech, confirmed information according to Barbosa’s ideas (1995); the position of the syllable stress, the joint of a fricative and lateral consonants, a nasal harmony, monomorphism for Latim negative prefixes and lexicalization are elements identified as contributor according to the intra-systemic viewpoint, which demonstrates that Manauara speech admits processes in favor of developing symmetries; the results also pointed out that the variable nasalization is a source applied to analyze phonetically similar forms, even if in a short predominance. In relation to extra-systemics, the data shows that the application of variable nasalization can be associated to a less prestigious design use of BP or less associated to the formal standard school. Key-words: Nasalized Vowels; Autosegmental Phonology; Manauara speech.